BICEPS BRACHII MUSCLE ACTIVATION IN TRAINED AND UNTRAINED SUBJECTS DURING ELBOW FLEXION WITHOUT VISUAL FEEDBACK (Fiep Bulletin - online, 2013)
Motor control is performed based on the integration of the nervous, musculoskeletal, and sensory systems, resulting from the previous structure of the movement along with a regulation via sensory feedback. Prior to the start of the movement execution, the muscles are activated with the goal of preparing the movement action seeking for a greater motor efficiency. In this manner, during an movement action, a regulation of muscle activation occurs with the sensorial information coming from the surrounding. Objective: The present study aimed to compare the muscle activation of the biceps brachii between trained and untrained subjects when performing elbow flexion without visual feedback. Methods: The sample constituted of 4 trained and 4 untrained subjects, being considered trained those who took part in strength training for at least the previous 6 months. The test consisted of performing the elbow flexion with a load equivalent to 80% of 1-RM, as defined by a 1-RM test, with eyes covered and an underhand grip. The electromyography signal was recorded with disposable surface electrodes (MediTrace) in the 5 seconds prior to the movement execution and throughout the exercise. Hence, the RMS value for the muscle analyzed was obtained and a statistical analysis with t-tests was used (p < 0.05). Results: The statistical analysis revealed greater (p < 0.02) anticipated activation of the biceps brachii muscles for trained subjects compared to untrained subjects. The results also demonstrate a tendency for greater muscle activation throughout the movement for trained subjects, although this difference did not reach statistical significance. Thus, the data suggest trained subjects present a more consistent structure prior to the movement, that is, they presented a better planning of action that is more efficient. Conclusion: The results mentioned demonstrate that trained subjects present a movement strategy that is more efficient in the resulting action of a better structure of movement. In this manner, the data reveal that the regular practice of exercise allowed the storage of characteristics which were specific to the movement by trained subjects, generating a better preparation that was more efficient, which is similar to findings in the literature.
Keywords: motor control; electromyography; strength training